2007
DOI: 10.1038/sj.ijo.0803545
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interaction and the GNB3 gene in the Atherosclerosis Risk in Communities Study

Abstract: Objective: The purpose of this study was to investigate the interaction between the G-protein beta-3 (GNB3) 825C4T polymorphism and physical activity in relation to prevalent obesity and hypertension. Research methods and procedures: The GNB3 825C4T genotype was measured in a sample of 14 716 African Americans (AAs) and whites from the Atherosclerosis Risk in Communities (ARIC) study, and logistic regression was used to test for genetic effects and gene-environment interactions. Results: The GNB3 825C4T varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…This observation is consistent with the results of Abdel-Aziz et al, who described that the association of obesity with TT genotype of rs1799983 polymorphism increased the risk to develop premature coronary artery disease in Egyptians [11]. Moreover, previous studies have identified the influence of obesity on the relationship between different polymorphisms and BP levels or hypertension among adults and children [35][36][37]. Initial epidemiological studies suggesting a relationship between obesity and BP levels have been supported with the understanding of potential mechanisms involved in both conditions, such as vascular and systemic insulin resistance, dysfuntion of the sympathetic nervous system and the renin-angiotensin-aldosterone system, among other pathogenetic factors [10,38].…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with the results of Abdel-Aziz et al, who described that the association of obesity with TT genotype of rs1799983 polymorphism increased the risk to develop premature coronary artery disease in Egyptians [11]. Moreover, previous studies have identified the influence of obesity on the relationship between different polymorphisms and BP levels or hypertension among adults and children [35][36][37]. Initial epidemiological studies suggesting a relationship between obesity and BP levels have been supported with the understanding of potential mechanisms involved in both conditions, such as vascular and systemic insulin resistance, dysfuntion of the sympathetic nervous system and the renin-angiotensin-aldosterone system, among other pathogenetic factors [10,38].…”
Section: Discussionsupporting
confidence: 92%
“…So, while there are many obstacles yet to surmount before genomic medicine becomes a reality (8,11,22), we can anticipate that future screening for genomic factors predicted to result in an adverse response of an at-risk phenotype to exercise prescription can improve treatment in susceptible patients. Preliminary findings in the areas of exercise and insulin sensitivity (5,28,29) and exercise and obesity (12,26) suggest that such genomic factors are being identified. While we await additional discoveries, exercise should certainly remain the first line of prescription for the many phenotypes positively impacted by this important treatment; however, we can recognize that this standard of care is not optimal for some patients and envision the future application of genomic information to improve and individualize exercise prescription.…”
mentioning
confidence: 99%
“…14,23,26 The current study demonstrates the interaction effect of GNB3 C825T and eNOS G894T polymorphisms on carotid IMT in young adults. This observation on a community-based cohort is noteworthy in that the participants are free of selection bias of studies involving relatively older adults with clinical CV morbidity.…”
Section: Discussionmentioning
confidence: 72%
“…An 80-bp product was amplified using 0.9 µmol/l each of the forward primer 5′-TCCCACGAGCATCATCTG-3′ and the reverse primer 5′-TCGTCGTAGCCAGCGAATAGT-3′, 0.2 µmol/leach of the sequence-specific probes 5′-6FAM-CATCACGTCCGTGGCCTTCTCC-TAMRA-3′ and 5′-VIC-CATCACGTCTGTGGCCTT CTCCCT-TAMRA-3′, 1 × TaqMan Universal PCR master mix containing AmpliTaq Gold DNA polymerase and 3 ng DNA in a 5.5 µl reaction volume. 23 Based on the analysis of 67 pairs of blind duplicates, there was 100% concordance in genotyping.…”
mentioning
confidence: 99%